"No hablo francés" : El traductor público como intérprete en sede judicial - Bertone, Martín (2019)
Abstract: This chronicle is aimed at reflecting the public's general lack of knowledge about the role of translators/interpreters when serving as court expert witnesses, and the hindrances that collecting professional fees at court entails. It also describes the procedures to be followed upon the expert witness' failure to act for reasons beyond his or her control.